The Criminalization Of Non-Consensual Deepfake Acts From The Perspective Of Positive Criminal Law And Human Rights Protection - Anggada Perkasa (jurnal.unprimdn.ac.id, 2026)
The development of generative artificial intelligence technology has given rise to the phenomenon of deepfakes, which involve the manipulation of a person's face, voice, or body language into synthetic audiovisual content that resembles the original. When this technology is used without the consent of the manipulated subject, particularly in the form of sexually suggestive content, fraud, or defamation, serious legal issues arise because Indonesian positive criminal law does not yet have norms that specifically and comprehensively regulate such acts. This study aims to analyze the position of non-consensual deepfakes within the framework of Indonesian positive criminal law and examine the urgency of their criminalization from the perspective of human rights protection. This study uses a normative juridical method with a legislative approach, a conceptual approach, and a case approach. The research findings indicate that relevant provisions are partially covered in the Electronic Information and Transactions Law, the Pornography Law, the Personal Data Protection Law, the Sexual Violence Law, and Law Number 1 of 2023 concerning the Criminal Code, which came into effect on January 2, 2026, specifically Articles 172 and 407 concerning pornography and Article 492 concerning fraud. However, these provisions do not explicitly address the elements of non-consent and the synthetic nature of a person's image as separate locus delicti, so enforcement still relies on general articles not designed for AI-based crimes. From a human rights perspective, non-consensual deepfakes constitute a violation of the right to privacy, the right to honor and dignity, and have the potential to constitute a form of online gender-based violence. This research recommends the need for a specific criminal norm (lex specialis) that explicitly regulates non-consensual deepfakes, along with strengthened redress mechanisms for victims.